A novel microtubule depolymerizing colchicine analogue triggers apoptosis and autophagy in HCT‐116 colon cancer cells†. (March 2016) - Kumar, Ashok; Singh, Baljinder; Sharma, Parduman R.; Bharate, Sandip B.; Saxena, Ajit K.; Mondhe, D. M.
Abstract : Colchicine is a tubulin‐binding natural product isolated from Colchicum autumnale. Here we report the in vitro anticancer activity of C‐ring modified semi‐synthetic derivative of colchicine; N‐[(7S)‐1, 2, 3‐trimethoxy‐9‐oxo‐10‐(4‐phenyl‐piperidin‐1‐yl)‐5, 6, 7, 9 tetrahydrobenzo[a]heptalen‐7‐yl]acetamide (4h ) on colon cancer HCT‐116 cell line. The compound4h was screened for anti‐proliferative activity against different human cancer cell lines and was found to exhibit higher cytotoxicity against colon cancer cell lines HCT‐116 and Colo‐205 with IC50 of 1 and 0.8 μM respectively. Cytotoxicity of the compound to the normal fR2 breast epithelial cells and normal HEK293 human embryonic kidney cells was evaluated in concentration and time‐dependent manner to estimate its selectivity for cancer cells which showed much better selectivity than that of colchicine. Compound4h induced cell death in HCT‐116 cells by activating apoptosis and autophagy pathways. Autophagy inhibitor 3‐MA blocked the production of LC3‐II and reduced the cytotoxicity in response to4h, but did not affect apoptosis, suggesting thereby that these two were independent events. Reactive oxygen species scavenger ascorbic acid pretreatment not only decreased the reactive oxygen species level but also reversed4h induced cytotoxicity. Treatment with compound4h depolymerized microtubules and the majority of cells arrested at the G2/M transition. Together, these data suggest that4h has better selectivity and is a microtubule depolymerizer, which activates dual cell‐death machineries, and thus, it could be a potential novel therapeutic agent in cancer therapy. Copyright © 2016 John Wiley & Sons, Ltd.